Penilaian Mahasiswa PBSI Unsika Terhadap Keefektifan Penggunaan Google Colab Dalam Pembelajaran Coding - Amal, Bahar; Damayanti, Silvia; Khonsa, Aisyah Nabila; Zahra, Mutia Haristi; Rahmadhani, Vissi Aulia; Anggraeni, Windi; Zendrato, Kezia Davina Putri (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
The skills of processing and analyzing data are very important in various sectors, including education. Students of Indonesian Language and Literature Education (PBSI) use google colab to study data processing. The purpose of this research is to understand and analyze the assessment of using google colab in coding learning for students of the Indonesian Language and Literature Education (PBSI) with the research object limited to students from the 2022 and 2023 batches. The research method used is quantitative with a questionnaire as the data collection tool. The questionnaire consists of open-ended and closed-ended questions. The results of the questionnaire show that 64.8% of respondents indicated that they have been using google colab for less than three months. Therefore, the majority of respondents do not have a long usage period. The experience of easy access to google colab is demonstrated by the majority of respondents. As many as 70.4% of respondents admitted that google colab speeds up the data processing process. The use of Google Colab can enhance collaboration, as shown by the uneven distribution of responses from the respondents, with 55 respondents answering that it plays a “significant” role. The use of google colab is considered quite effective in coding education, as evidenced by 51 respondents stating so. Ease of access is a prominent advantage of google colab. It can be concluded that the assessment of Indonesian Language and Literature Education (PBSI) students regarding the effectiveness of using google colab in coding learning is positive.